2017
DOI: 10.1007/s00253-017-8277-6
|View full text |Cite
|
Sign up to set email alerts
|

Yeast response and tolerance to benzoic acid involves the Gcn4- and Stp1-regulated multidrug/multixenobiotic resistance transporter Tpo1

Abstract: The action of benzoic acid in the food and beverage industries is compromised by the ability of spoilage yeasts to cope with this food preservative. Benzoic acid occurs naturally in many plants and is an intermediate compound in the biosynthesis of many secondary metabolites. The understanding of the mechanisms underlying the response and resistance to benzoic acid stress in the eukaryotic model yeast is thus crucial to design more suitable strategies to deal with this toxic lipophilic weak acid. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…MFS transporter genes such as GE09014_g, GE09100_g, and GE09173_g in this study (Supplementary Table S3) were highly homologous with YLL028W (Tpo1), YLL028W (Tpo1), and YNL065W (Aqr1) in yeast. Tpo1 was demonstrated to confer resistance to benzoic acid in Saccharomyces cerevisiae, and under the controls of the Gcn4 and Stp1 transcription factors involved in the response to amino acid availability (Godinho et al, 2017). However, the sequences of these three genes are consistent in MDR isolate LT586 and fungicide sensitive isolate LT15 without point mutations.…”
Section: Discussionmentioning
confidence: 99%
“…MFS transporter genes such as GE09014_g, GE09100_g, and GE09173_g in this study (Supplementary Table S3) were highly homologous with YLL028W (Tpo1), YLL028W (Tpo1), and YNL065W (Aqr1) in yeast. Tpo1 was demonstrated to confer resistance to benzoic acid in Saccharomyces cerevisiae, and under the controls of the Gcn4 and Stp1 transcription factors involved in the response to amino acid availability (Godinho et al, 2017). However, the sequences of these three genes are consistent in MDR isolate LT586 and fungicide sensitive isolate LT15 without point mutations.…”
Section: Discussionmentioning
confidence: 99%
“…cerevisiae COQ2 [ 46 ]. If the specificity of Bz to various Coq2 homologs is not so strict, differences in the inhibitory effect of Bz on CoQ synthesis among different organisms might be due to differences in how effectively Bz is transported inside cells [ 47 ] and into mitochondria. On the contrary, the observation in this study that an inhibitory effect of 4-NB was not observed in S .…”
Section: Discussionmentioning
confidence: 99%
“…COQ2 and its homolog are interchangeable among species; S. cerevisiae COQ2 is functionally exchangeable with UbiA in E. coli [45] and an Arabidopsis PPT1 (COQ2) homolog with S. cerevisiae COQ2 [46]. If the specificity of Bz to various Coq2 homologs is not so strict, differences in the inhibitory effect of Bz on CoQ synthesis among different organisms might be due to differences in how effectively Bz is transported inside cells [47] and into mitochondria. On the contrary, the observation in this study For the pre-culture, PR110 yeast cells were cultivated in 10 mL YES for 1 day.…”
Section: Plos Onementioning
confidence: 99%
“…At this pH, there are larger microorganism populations especially represented by Lactobacillus spp, Bacillus spp and yeast that can easily grow (Ouoba et al, 2010;Abriouel et al, 2006;Abriouel et al, 2007). Mecanisms of acidic resistance L. plantarum and yeast have been documented (Zhao et al, 2019;Godinho et al, 2017). Henick-Kling et al (1989) demonstrated that throughout the development of wine, the pH acts on several levels: it participates in the selection of species according to their acid-resistance, it directs their metabolism and determines their speed especially of multiplication as evidenced by our results obtained on PCA culture medium (Henick-Kling et al, 1989).…”
Section: Discussionmentioning
confidence: 99%